1994
DOI: 10.1042/bj3040761
|View full text |Cite
|
Sign up to set email alerts
|

Specific activation of β-casein kinase by the inflammatory cytokines interleukin 1 and tumour necrosis factor

Abstract: Increases (5-fold) in the rate of phosphorylation of beta-casein were observed in extracts of human gingival fibroblasts that had been stimulated by interleukin 1 (IL-1) or tumour necrosis factor (TNF). The induced kinase was cytosolic and had little activity on alpha-casein. Its chromatographic behaviour on anion-exchange and gel-filtration columns was similar to that of beta-casein kinase, an enzyme detected originally in MRC-5 cells stimulated by IL-1 and TNF. Phosphopeptide maps of beta-casein confirmed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…The identification of Nek8 was based on a search for an IL-1 mediated ␤-casein kinase activity reported by Guesdon et al (21,22). Although we identified Nek8 activity in a homogenate from IL-1-treated rabbits that was absent in homogenates from naïve rabbits, we do not believe that Nek8 corresponds to the previously described activity.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The identification of Nek8 was based on a search for an IL-1 mediated ␤-casein kinase activity reported by Guesdon et al (21,22). Although we identified Nek8 activity in a homogenate from IL-1-treated rabbits that was absent in homogenates from naïve rabbits, we do not believe that Nek8 corresponds to the previously described activity.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies had reported the identification of a specific ␤-casein phosphorylating activity induced by IL-1, named ␤-casein kinase (21)(22)(23). This novel activity was shown to be specific for phosphorylating ␤-casein and not ␣-casein, and was distinct from any known mitogen-activated protein kinase or hsp27 kinase.…”
Section: Isolation Purification and Cloning Of Human Nek8 Andmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been demonstrated that late displacement of IL-1 from the type I receptor blocks transcription, suggesting that the continued presence of IL-1 on the IL-1RI is critical to amplification of IL-1-mediated biologic effects (26). While most intracellular effects of IL-1 occur rapidly and are short-lived, at least one potential mediator of IL-1 activity with sustained activity was described by Guesdon and coworkers, who demonstrated the persistent presence of active p-casein kinase (47). Transcriptional results mediated by this pathway have not yet been fully defined.…”
Section: Findings Of Western Blot Analysis Of Nf-kbmentioning
confidence: 99%
“…However, little definitive data have come forth delineating the post-receptor molecular events. TNF receptors do not contain an intrinsic kinase domain, and recently, the involvement of serine/threonine protein kinases, including the so-called mitogen-activated protein kinases (MAPKs), has been proposed by a number of investigators (13)(14)(15)(16)(17). MAPKs form a large family of serine/threonine protein kinases activated by separate cascades and are important mediators of signal transduction from the cell surface to the nucleus.…”
mentioning
confidence: 99%